Antioxidant activity and antibacterial evaluation of new thiazolin-4-one derivatives as potential tryptophanyl-tRNA synthetase inhibitors. (1st January 2019) - Stana, Anca; Vodnar, Dan C.; Marc, Gabriel; Benedec, Daniela; Tiperciuc, Brînduşa; Tamaian, Radu; Oniga, Ovidiu
Abstract: The rapid emergence of bacterial resistance to antibiotics currently available for treating infectious diseases requires effective antimicrobial agents with new structural profiles and mechanisms of action. Twenty-three thiazolin-4-one derivatives were evaluated for their antibacterial activity by determining the growth inhibition zone diameter, the minimum inhibitory concentration (MIC), and the minimum bactericidal concentration (MBC), against gram-positive and gram-negative bacteria. Compounds 3a–c, 3e–h, 6b–c and 9a–c expressed better MIC values than moxifloxacin, against Staphylococcus aureus . Compounds 3h and 9b displayed similar effect to indolmycin, a tryptophanyl-tRNA ligase inhibitor. Due to their structural analogy to indolmycin, all compounds were subjected to molecular docking on tryptophanyl-tRNA synthetase. Compounds 3a–e, 6a–e, 8 and 9a–e exhibited better binding affinities towards the target enzymes than indolmycin. The antioxidant potential of the compounds was evaluated by four spectrophotometric methods. Thiazolin-4-ones 3e, 6e and 9e presented better antiradical activity than ascorbic acid, trolox and BHT, used as references. Abstract :